A THREE-DIMENSIONAL REVOLUTION IN MEDICINE—THE USE OF 3D PRINTING TECHNOLOGY IN ORTHOPEDICS, SURGERY, AND NEUROSURGERY - Wirginia Bertman; Bartłomiej Czarnecki; Jan Nowak; Barbara Kujawa; Bartosz Zwoliński; Wiktor Kubik; Kacper Sukiennicki; Natalia Kołdej; Zuzanna Kępczyńska; Katarzyna Szewczyk; Kamil Borysewicz; Klaudia Romejko (International Journal of Innovative Technologies in Social Science, 2025)
3D printing has become one of the most dynamically developing technologies in medicine in recent years, and the use of products made using a 3D printer is increasingly influencing medicine in areas such as medical education, surgery planning, personalizing implants and tissue engineering. Despite how quickly this field is developing, research and discussions are still ongoing whether this technology is safe for the patient, cost-effective and how it affects the health care system in the long term. The aim of this work is to present the applications of 3D printing in medicine and to assess its benefits, development prospects and limitations. Brief description of the State of Knowledge: The narrative review presents the current state of knowledge about 3D printing in medicine, with particular emphasis on the operation of this technology in the fields of orthopedics, surgery and neurosurgery. The most popular methods of producing 3D models, the main advantages and disadvantages of the technology and predictions for the future development of the field of 3D printing in the development of medicine were discussed. Methodology: A narrative literature review was conducted. The analysis covered scientific publications on 3D printing in healthcare. Sources from 2019-2025 were included, searching for terms such as: “3D printing in medicine,” “additive manufacturing in healthcare,” “personalized implants,” “3D printing,” “surgical models,” and “the future of 3D printing in medicine.”